Exploring Local Wisdom: Improving Basic Skills in Heat Transfer material through Developing a Physics Module Based on Smoked Fish - Sri Wina Oktavia; Nikma Nur Qoidah; Irma Giorgadze; Camila Gasparin (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aim of this research is to determine the differences in the use of physics modules based on local wisdom of smoked fish in heat transfer material. Methodology: This research adopts a research and development (R&D) approach. The samples taken for this research were two classes at the school, with each class consisting of 30 students. The data collection technique in this research was carried out through the use of a questionnaire as the main instrument. The data analysis technique in this research involves a series of systematic steps to test assumptions and test hypotheses. Main Findings: Based on the results of the T-test, students' responses to the use of a physics module based on the local wisdom of smoked fish in one of the high schools in Eastern Sumatra. The T test results obtained a sig value. (2-tailed) 0.037 < 0.05 so it can be concluded that there are differences in student responses who use the physics module based on the local wisdom of smoked fish. Novelty/Originality of this study: Delving into local wisdom, this innovative approach transforms the teaching of heat transfer in physics by crafting a specialized module inspired by the traditional technique of smoking fish. Through this unique lens, students not only enhance their fundamental skills but also gain a profound appreciation for the seamless integration of indigenous practices into scientific education.